2010
DOI: 10.1038/ncomms1093
|View full text |Cite
|
Sign up to set email alerts
|

Protein-binding assays in biological liquids using microscale thermophoresis

Abstract: Protein interactions inside the human body are expected to differ from the situation in vitro. This is crucial when investigating protein functions or developing new drugs. In this study, we present a sample-efficient, free-solution method, termed microscale thermophoresis, that is capable of analysing interactions of proteins or small molecules in biological liquids such as blood serum or cell lysate. The technique is based on the thermophoresis of molecules, which provides information about molecule size, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
852
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 978 publications
(902 citation statements)
references
References 36 publications
16
852
1
7
Order By: Relevance
“…Serial dilutions of the non-labelled GAPDH molecules (10 ml each) were mixed with 10 ml of the fluorescently labelled transferrin molecule. The final sample was loaded into Monolith NT.115 capillaries, followed by analysis with the Monolith NT.115 instrument (Nanotemper) 61 .…”
Section: Methodsmentioning
confidence: 99%
“…Serial dilutions of the non-labelled GAPDH molecules (10 ml each) were mixed with 10 ml of the fluorescently labelled transferrin molecule. The final sample was loaded into Monolith NT.115 capillaries, followed by analysis with the Monolith NT.115 instrument (Nanotemper) 61 .…”
Section: Methodsmentioning
confidence: 99%
“…The detailed principle and theory have been reported before. [31] In the present study, it relies on the detection of the difference of fluorescence signal intensity caused by the directional movement of FITC label on the hIAPP [11][12][13][14][15][16][17][18][19][20] (FITClabeled hIAPP [11][12][13][14][15][16][17][18][19][20] ) along the temperature gradient in microenvironment. The affinities of molecular interactions were measured by titration experiments in the equilibrium state.…”
Section: Background Of Thermophoresismentioning
confidence: 99%
“…Rln(K d ) and 1/T was plotted in the inset of Figure 5 to obtain the thermodynamic parameters ΔH and ΔS on the basis of van't Hoff plot. [31] The linear regression equation was established and listed in Table 2, and the types of binding events were determined by the principles of thermodynamics. [30] The results showed that the interaction between hIAPP [11][12][13][14][15][16][17][18][19][20] and these lipopeptide inhibitors is all spontaneous exothermic processes because of the negative change in Gibbs free energy and enthalpy changes.…”
Section: Thermodynamic Parameters By Mstmentioning
confidence: 99%
“…G protein binding. We next used a microscale thermophoresis technique (35) to investigate the ability of the TSHR ICD mimetics to bind recombinant purified Ga subunits. TSHR is remarkable in its ability to activate all known G protein isoforms (21)(22)(23).…”
Section: Construction Of Tshr Icd Mimeticsmentioning
confidence: 99%